SERVICE QUALITY AND PERFORMANCE OF ACADEMIC ADMINISTRATION EMPLOYEES ON STUDENT SATISFACTION - Delly Mustafa; Sitti Chaeriah Ahsan; Muhammad Aris; Risma Niswaty; Tunggul Prasodjo (Universitas Padjadjaran, 2022)
Higher education institutions should guarantee student satisfaction, not only in academic services such as the teaching and learning process, but also include administrative services, administrative and academic processes. This study aims to determine and analyze the quality of service, determine and analyze the performance of academic administrative employees, determine and analyze the level of student satisfaction, determine the effect of service quality and academic staff performance on student satisfaction at the Faculty of Social Sciences. Science and Law, Universitas Negeri Makassar. The research method used is causal associative quantitative type, the total population is 4. 588 with a research sample of 98 respondents. Data collection techniques are questionnaires, observation, and documentation with data analysis using descriptive analysis and multiple linear regression analysis. The effect of service quality and performance of administrative staff on student satisfaction is 53.10%. The magnitude of the effect is 53.10%, indicating that service quality and performance affect student satisfaction at the Faculty of Social Sciences and Law (FIS-H), Universitas Negeri Makassar, other factors contribute 46.90 percent to student satisfaction.